Improved pulsed field magnetisation in MgB2 trapped-field magnets - Moseley, D; Matthews, GABM; Zhou, D; Speller, S (IOP Publishing, 2021)
Bulk superconductors can act as trapped-field magnets with the potential to be used for many applications such as portable medical magnet systems and rotating machines. Maximising the trapped field, particularly for practical magnetisation techniques such as pulsed field magnetisation (PFM), still remains a challenge. PFM is a dynamic process in which the magnetic field is driven into a superconducting bulk over milliseconds. This flux motion causes heating and a complex interplay between the magnetic and thermal properties. In this work, the local flux density during PFM in a MgB2 bulk superconductor has been studied. We find that improving the cooling architecture increases the flux trapping capabilities and alters the flux motion during PFM. These improvements lead to the largest trapped field (0.95 T) for a single MgB2 bulk sample magnetised by a solenoidal pulsed field magnet. The findings illustrate the fundamental role bulk cooling plays during PFM.